A new approach of using polyethylene frits for the quantification of sulphur in copper metals by isotope dilution LA-ICP-MS and comparison with conventional IDMS techniques. Issue 9 (19th July 2018) - Phukphatthanachai, Pranee; Vogl, Jochen; Traub, Heike; Jakubowski, Norbert; Panne, Ulrich
Abstract : Polyethylene (PE) frits were used to quantify sulphur in copper and its alloys by isotope dilution combined with LA-ICP-MS as an alternative approach to conventional sample preparation. Abstract : Polyethylene (PE) frits were used to quantify sulphur in copper and its alloys by isotope dilution combined with LA-ICP-MS as an alternative approach to conventional sample preparation: the copper samples were spiked, the spiked samples were dissolved, the resulting solutions were absorbed in the PE frits and finally the PE frits were analysed by LA-ICP-MS. A prerequisite for such a support material is a low sulphur blank and thus PE was selected for this purpose. The absorption efficiency of the PE frits was studied for varying sulphur amounts ranging from 2 μg S to 80 μg S showing that more than 99.5% of the loaded sulphur was absorbed by the frit. The so prepared PE frits were measured by LA-ICP-MS and yielded a good linearity ( R 2 = 0.999) for the sulphur ion intensities corresponding to sulphur amounts up to 40 μg S; the associated sensitivity is approximately 3.4 × 10 4 cps μg −1 for 32 S. For the validation of the developed procedure the reference materials BAM-M376a, BAM-228 and BAM-227 were applied such that 2 μg S, 5 μg S and 11 μg S were absorbed in the PE frits, respectively. These samples were pre-quantified for the adsorbed sulphur amount by external calibration LA-ICP-MS yielding sulphur amounts of 0.9 μg, 5.1 μg and 8.5 μg (quantified for 32 S only), respectively. Relative standard deviations of the isotope ratios were below 5% in average ( n = 3 lines) in all cases (except for the pure spike solution). These samples were then analysed by LA-ICP-IDMS and the measurement results were validated by comparing them with the results obtained by conventional ICP-IDMS. The obtained relative expanded measurement uncertainties ranged between 10% and 26%. Pearson's coefficient was used to express the correlation between both techniques; the obtained value was 0.999 demonstrating a strong correlation. Contrary to most published LA-ICP-IDMS procedures, the developed procedure enables SI-traceability for the measurement results. The metrological traceability to the SI for the sulphur mass fractions in copper was established by an unbroken chain of comparisons, each accompanied by an uncertainty budget. Thus, the measurement results are considered reliable, acceptable and comparable within the stated measurement uncertainty. The metrological traceability chain from the kg down to mass fraction in the samples obtained by LA-ICP-IDMS is presented as well.